Case report: Exploring chemoradiotherapy-induced leukoencephalopathy with 7T imaging and quantitative susceptibility mapping - Celardo, Gaetano; Scaffei, Elena; Buchignani, Bianca; Donatelli, Graziella; Costagli, Mauro; Cristofani, Paola; Canapicchi, Raffaello; Pasquariello, Rosa; Tosetti, Michela; Battini, Roberta; Biagi, Laura (Frontiers in Neurology, 2024)
Chemotherapy and radiotherapy are widely used in the treatment of central nervous system tumors and acute lymphocytic leukemia even in the pediatric population. However, such treatments run the risk of a broad spectrum of cognitive and neurological deficits. Even though the correlation with cognitive decline is still not clear, neuroradiological defects linked to white matter injury and vasculopathies may be identified. Thanks to the use of 7T MRI it is possible to better define the vascular pattern of the brain lesions with the added advantage of identifying their characteristics and anatomical localization, which, however, are not evident with a conventional brain scan. Moreover, the use of Quantitative Susceptibility Mapping (QSM) makes it possible to discriminate between calcium deposits on vessels (chemo-radiation-induced) and hemoglobin deposition in radio-induced cavernomas, speculating, as a result, about the pathophysiology of iatrogenic brain damage. We describe the case of a 9 year-old boy with a T-type acute lymphoid leukemia who had previously been treated with polychemotherapy and high-dose RT. To better define the child's neuroradiological pattern, 7T MRI and QSM were performed in addition to conventional imaging examinations. Our case report suggests the potential usefulness of a QSM study to distinguish radio-induced vascular malformations from mineralizing microangiopathy.